To solve the expression \( 9 + 2^2 \div 4 \) step by step, we start with the exponent.
- Calculate the exponent: \[ 2^2 = 4 \]
Now we can replace \( 2^2 \) with \( 4 \) in the expression:
\[ 9 + 4 \div 4 \]
- Next, according to the order of operations (PEMDAS/BODMAS), we perform the division before the addition: \[ 4 \div 4 = 1 \]
Now we can replace \( 4 \div 4 \) with \( 1 \):
\[ 9 + 1 \]
- Finally, calculate \( 9 + 1 \): \[ 9 + 1 = 10 \]
So the final answer is:
\[ 9 + 2^2 \div 4 = 10 \]
The answer can be summarized as:
\[ 9 + [4] \div 4 = 10 \]